Determination of the absolute configuration of (-)-(2R)-succinic-2-d acid by neutron diffraction study: unambiguous proof of the absolute stereochemistry of the NAD+/NADH interconversion. - Yuan, H S (1988)
The absolute configuration of the CHD group (D = deuterium) in (-)-(2R)-succinic-2-d acid, as prepared from (-)-(2S,3R)-malic-3-d acid, has been shown unambiguously to be R by the technique of single-crystal neutron diffraction. The optically active cation (+)-phenylethylammonium was used as the chiral reference. The structure of [C6H5CH3CHNH3]+[HOOCCH2CHDCOO]- has been studied with x-ray diffraction at room temperature and neutron diffraction at 100 K. Crystal data from the neutron diffraction analysis of the phenylethylammonium salt of the title compound at 100 K: space group P21; a = 8.407(2) A, b = 8.300(4) A, c = 8.614(2) A, beta = 91.20(3) degrees; unit cell volume = 600.9(3) A3, zeta = 2 (numbers in parentheses are the estimated standard deviations). Final agreement factors are R(F2) = 0.0355 and R(wF2) = 0.0457 for 1690 independent neutron reflections and 297 parameters varied. The result confirms the stereochemistry of the malate/succinate transformation, as well as the NAD+/NADH interconversion, and demonstrates the usefulness of the single-crystal neutron diffraction method for determining the absolute configuration of molecules having a chiral monodeuteriomethylene group.